Effect of the Stepped Spillway Geometry on the Flow Energy Dissipation - Karim R. Gubashi; Saad Mulahasan; Zuhair A. Hacheem; Ali Q. Rdhaiwi (Civil Engineering Journal, 2024)
In this research, flume experiments were conducted on stepped weirs to investigate the effect of step shape on the energy dissipation of flow. Four configurations with a constant number of steps were considered, namely, horizontal steps, inclined steps, horizontal steps with rounded sills, and ‎inclined steps with rounded sills. The slopes of inclined steps were 13% and 23%, and the diameters of the rounded sills of the step ends were 10 and 15 cm. The majority of previous studies focused on energy dissipation in stepped weirs in horizontal and inclined steps. In this research, new step geometries were used, such as horizontal steps with rounded sills and inclined steps with rounded sills. Dimensional analysis was applied to correlate the different variables affecting the flow hydraulics. Flow rates in the range of 0.61-9.12 lit/sec were used with each step shape. Results showed that the inclined steps with rounded sills had the highest flow energy dissipation in comparison to the other types. Rounded sills at the end of steps had more effective energy dissipation than did the horizontal step. However, the 23% inclination slope with rounded sills of a 7.5 cm radius was the most effective in dissipating flow energy. Doi: 10.28991/CEJ-2024-010-01-09 Full Text: PDF